Leg Configuration and Foot Motion Space Estimation of a Quadruped Robot Considering Waist Characteristics - Zhang Yongyue; Wu Binghui; Li Min; Deng Yangtai; Chen Yuan (Jixie chuandong)
In order to improve the adaptability of the quadruped robot to the complex road surface, a quadruped robot with three degrees of freedom on one leg was presented. Firstly, based on the virtual prototyping technology, the ratio of the lower leg was optimized, and the best ratio of the lower leg was obtained, which took into account both the speed and the motion stability. Based on this, the waist length of the robot was optimized by using the optimization feature of the genetic algorithm and taking the space utilization rate as the objective function. Then, the forward kinematics analysis was carried out based on the D-H method. Finally, the Monte Carlo estimation of the foot reachable space was carried out by using the Matlab software. The ideal standing height and step length of the robot were obtained, which laid a foundation for the subsequent gait planning of the robot.